Annotated legal documents on Islam in Europe: : Czech Republic - Němec, Damián (Annotated legal documents on Islam in Europe, 2021)
Foreword by the Editors -- General Introduction -- 1. Status of Religious Communities -- 2. Relations between the State and Islam -- 3. State Support for Islamic Religious Communities -- 4. The Islamic Community of the Czech Republic -- 5. Muslims and the Law on Issues of Social Integration -- 6. Mosques and Prayer Houses -- 7. Burial and Cemeteries -- 8. Education and Schools -- 9. Further and Higher (Tertiary) Education -- 10. Islamic Chaplaincy in Public Institutions -- 11. Employment and Social Law -- 12. Islamic Slaughter and Food Regulation -- 13. Islamic Goods and Services -- 14. Islamic Dress -- 15. Criminal Law -- 16. Family Law -- Bibliography -- Index.